2013
DOI: 10.1002/pssa.201330020
|View full text |Cite
|
Sign up to set email alerts
|

Growth, characterization, and properties of bulk SnO2 single crystals

Abstract: SnO2 is a semiconductor with a wide optical bandgap (3.5 eV), which makes it an attractive transparent semiconducting oxide (TSO) for electronic and opto‐electronic applications. At elevated temperatures it is, however, much more unstable than other TSOs (such as ZnO, Ga2O3, or In2O3). This leads to a rapid decomposition even under very high oxygen pressures. Our experiments showed that stoichiometric SnO2 does not melt up to 2100 °C, in contradiction to earlier published data. Bulk SnO2 single crystals, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 39 publications
(58 reference statements)
1
42
0
Order By: Relevance
“…There are only a few studies in the oxide MBE literature using evaporation of the metal oxide from an effusion cell. [19][20][21][22][23] Vapor pressure data indicate that SnO 2 sublimes in the form of suboxides (SnO x ) with vapor pressures sufficient for reasonable flux rates at practically feasible effusion cell temperatures, i.e., ∼10 −5 Torr at 1300 • C. 24 Figure 1(b) shows RHEED during BaSnO 3 growth on (001)SrTiO 3 at a substrate temperature of 800 • C, using the SnO 2 source. The RHEED pattern is streaky from the start of the growth and remains so throughout, without any significant decrease in the intensity.…”
mentioning
confidence: 99%
“…There are only a few studies in the oxide MBE literature using evaporation of the metal oxide from an effusion cell. [19][20][21][22][23] Vapor pressure data indicate that SnO 2 sublimes in the form of suboxides (SnO x ) with vapor pressures sufficient for reasonable flux rates at practically feasible effusion cell temperatures, i.e., ∼10 −5 Torr at 1300 • C. 24 Figure 1(b) shows RHEED during BaSnO 3 growth on (001)SrTiO 3 at a substrate temperature of 800 • C, using the SnO 2 source. The RHEED pattern is streaky from the start of the growth and remains so throughout, without any significant decrease in the intensity.…”
mentioning
confidence: 99%
“…The electron mobility of bulk SnO 2 is up to 200 cm 2 V À1 s À1 . [5] This value decreases to ,1.0 cm 2 V À1 s À1 for porous nanomaterial, [6] nevertheless, is two orders of magnitude higher than that of TiO 2 . Hossain et al have reported a very high photocurrent density that was achieved with quantum dots-sensitised solar cells using SnO 2 as electron-transport material.…”
Section: Introductionmentioning
confidence: 85%
“…Another growth from the vapor phase includes the PVT [65][66][67][121][122][123], which involves the decomposition of SnO 2 into SnO and oxygen at high temperatures (vaporization zone) and reoxidation of SnO to SnO 2 at lower temperatures (growth zone). Marley et al [65,121] used an alumina ceramic muffle tube furnace with a vaporization zone held at 1650 C and a longer zone with a temperature gradient of 20 K/in, where crystal growth occurred on a removable mullite tube.…”
Section: Snomentioning
confidence: 99%
“…Galazka et al [67] applied the PVT method with an iridium crucible containing the SnO 2 starting material, which was covered by a ring-shaped seed holder acting as a nest for a circular sapphire or rutile crystal seed (or substrate). The crucible was placed inside thermal insulation and was heated up inductively.…”
Section: Snomentioning
confidence: 99%
See 1 more Smart Citation